Targeting delivery and minimizing epidermal diffusion of tranexamic acid by hyaluronic acid-coated liposome nanogels for topical hyperpigmentation treatment. (1st January 2021) - Liu, Ying; Han, Yue; Zhu, Tingting; Wu, Xianglei; Yu, Wenxin; Zhu, Jiafang; Shang, Ying; Lin, Xiaoxi; Zhao, Tianlan
Abstract: Hyperpigmentation is a common complaint and distressing problem in dermatology, and tranexamic acid (TA) is an effective treatment agent but limited by the delivery to melanocytes in the epidermis. Herein, a novel TA naogels (named HA/TA-LP), combining the advantages of liposomes and hyaluronic acid (HA), are prepared and assessed for topical hyperpigmentation treatment with targeting delivery and minimizing epidermal diffusion. Morphological characteristics indicate numerous TA-loaded liposomes packed in HA gels. In vitr o cell studies using human A375 melanoma cells show that HA/TA-LP can promote the uptake of TA by targeting delivery with resulting inhibition of tyrosinase activity and melanin production. Guinea pigs are used to construct hyperpigmentation models and investigate the topical delivery and treatment efficacy of HA/TA-LP. In vivo topical delivery studies indicate HA/TA-LP realize the effective delivery into melanocytes with an ideal balance of effective permeability and minimizing epidermal diffusion. Subsequently, hyperpigmentation treatment assessments reveal that HA/TA-LP inhibit tyrosinase activity and melanin production under the radiation of UVB. Our study identifies favorable properties of HA/TA-LP for treating hyperpigmentation, and provides an experimental basis for further clinical application.